The role of culture and financial literacy on the actual use digital payment systems for MSMEs in Rantepao city - Stefani Marina Palimbong; Pompeng, Olivia Devi Yulian (Jurnal Ekonomi, 2024)
This research aims to analyze and determine the influence of culture and financial literacy on the actual use of digital payments by MSMEs in Rantepao City. Study This use approach quantitative . The object under study are MSME owners in Rantepao City, Regency North Toraja . Data obtained through survey with instruments, ie questionnaire And method taking sample used _ is random sampling method . Data analyzed with using the SPSS 20 statistical program . The research results concluded that culture had a significant effect on the actual Use Digital Payment System, financial literacy has a significant effect on Actual Use Digital Payment System, culture and financial literacy simultaneously influence Actual Use Digital Payment System